Let's talk health – the textual efficiency of the discourse of healthcare articles in online women's magazines cosmopolitan (a comparative study) - Radostina Iglikova (European Journal of Bioethics, 2013)
The following article deals with some strategies for enhancing textual efficiency in healthcare articles and is based on a corpus of texts from online women`s magazines. Here effficiency is understood in the sense beaugrande and Dressler suggest, i.e. as a principle which controls textual communication, so that texts are used with "a minimum expenditure of effort by the participants". The object of analysis are articles from three online editions of the Cosmopolitan magazine – the American, british and bulgarian variants respectively. The linguistic and socio-cultural specificities of the different audiences reflected in the choice of topics, their treatment, textual form and structure are of particular interest and are therefore regarded as a crucial part of the underlying context, alongside the role of the nature of the medium itself.